Debulking Surgery Plus Radiation: Treatment Choice for Unresectable Stage III Thymic Carcinoma - Zhai, Yirui; Hui, Zhouguang; Gao, Yushun; Liang, Jun; Zhou, Zongmei; Wang, Luhua; Feng, Qinfu (The Thoracic and Cardiovascular Surgeon, 2020)
Background Total resection may not be achieved in patients with thymic carcinoma, particularly those with Masaoka stage III disease. Debulking surgery plus postoperative radiotherapy and radiation alone are treatment options for such patients. We aimed to compare the overall survival (OS) between patients with thymic carcinoma who underwent debulking surgery plus postoperative radiotherapy and those who underwent radiation alone.Methods This was a single-center retrospective study of patients histologically diagnosed as having Masaoka stage III thymic carcinoma between January 1980 and January 2010. Patients were classified into the following groups according to treatments received: debulking surgery plus radiotherapy (group A) and radiotherapy alone (group B). Data on demographics, histology, invasion, radiotherapy, chemotherapy, and survival were collected. Survival time was calculated and compared between the groups using the Kaplan–Meier method. Toxicities were graded according to the National Cancer Institute Common Terminology Criteria for Adverse Events version 3.0.Results Of the 47 enrolled patients, 26 and 21 patients were categorized into groups A and B, respectively. There are no significant differences in the Eastern Cooperative Oncology Group performance status score, histological type, great vessel invasion, and chemotherapy proportion between the groups. The median radiation dose was 60 Gy in both groups. The 5-year OS rates were 54.4 and 0% in groups A and B, respectively (p = 0.019). No operation-induced mortality was recorded.Conclusion For patients with unresectable Masaoka stage III disease, debulking surgery with radiotherapy is preferred, as this was proven to be more efficient than the radiation-alone procedure.
Keywords: debulking surgery; radiation; thymic carcinoma